The Notary Position in The System of Corporation and Legal Contract Industry in Bangladesh - Misty, Mousume Akter (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Notaries play a vital role in preserving the integrity of legal transactions and upholding justice in the domain of legal systems. Examining the function of notaries and their adherence to ethical codes in Bangladesh is crucial as the nation develops and negotiates difficult legal issues. In order to clarify this important facet of the legal system, a thesis proposal titled